Description of The Learning Environment in Office Application Training in Prima Data Padang Training Course Institution - Yolanda Rismawati; Vevi Sunarti (Universitas Negeri Padang, 2021)
This research is motivated by the high learning outcomes of students in the Office Application training at the Prima Data Padang Training Course Institute (LKP), this is presumably due to the learning environment. This study aims to see a picture of the learning environment in terms of the place of study, learning tools, atmosphere / conditions, time and interaction in learning.This type of research is a quantitative descriptive study. The population in this study were students of the Office Application training at Prima Data Padang Training Course Institute (LKP). The technique of sampling is simple random sampling, the sample taken is 75% of the population, namely 18 people. The data collection technique used a questionnaire. Meanwhile, the data collection tool is google form. The data analysis technique uses the percentage formula.The results showed that first, the learning environment in the Office Application training at the Prima Data Padang Training Course Institute (LKP) from the point of view of the place of learning was said to be very supportive. Second, the learning environment in the Office Application training at the Prima Data Padang Training Course Institute (LKP) in terms of learning tools is said to be very supportive. Third, the learning environment in the Office Application training at the Prima Data Padang Training Course Institute (LKP) in terms of atmosphere / conditions is said to be supportive. Fourth, the learning environment in the Office Application training at the Prima Data Padang Training Course Institute (LKP) from a time perspective is said to be supportive. Fifth, the learning environment in the Office Application training at the Prima Data Padang Training Course Institute (LKP) from the association is said to be very supportive. Keywords: learning environment, non-formal education, training, LKP.